Small‐Capacity Gold Production Tests From Waste Desktop Computers. Issue 2 (December 2015) - Sinioros, Panagiotis; Lasithiotakis, Michael; Akidil, Mehmet Emin
Abstract : This article describes a procedure for the hydrometallurgical recovery of gold from waste computer printed circuit boards (PCBs) and central processing units (CPUs). The wastes processed within the recovery installation described in this article were derived from desktop computers, the parts of which were manually sorted to select those components found to be rich in gold content. X‐ray fluorescence measurements showed that considerable amounts of gold are contained in the "finger" terminals of the PCBs as well as in the CPUs. This article describes the chemical processes for recovering gold from these parts. In addition, the article covers the emissions control apparatus that is capable of eliminating the nitrogen oxides (NOx) and sulfur dioxide (SO2) emissions produced by the recovery process. The main costs arising from the overall procedure are for personnel utilization. Approximately 60 work hours from one worker are required to process 1.75–1.85 tons of unprocessed desktop computer waste to produce gold in the form of sediments. The quantity of gold recovered from this amount of waste computers can reach up to 35 grams with a standardized purity of 21 karats. The overall recovery procedure takes eight consecutive calendar days to accomplish.